РОЛЬ СТИХОТВОРЕНИЙ В ПРОЗЕ В ТВОРЧЕСТВЕ АЛЬФИ ГАСЫМОВА - Кулиева, С. Ш. (Eurasian Journal of Philology Science and Education, 2015)
The period of 1960-80 when the well-known Azerbaijan prose writer Alfi Gasymov created, draw attention an urgency of problems, a genre variety, variety of relations to problems of the person, a society, the nature, large number of talented, intellectual masters of a feather.